Análisis del clima laboral y propuesta para mejorar la satisfacción de los colaboradores de una institución pública encargada de la defensa de los derechos de los niños, niñas, adolescentes y adultos mayores, con sede en la ciudad de Quito, en el período septiembre 2016-julio 2017 : Sistematización de la experiencia - Mármol López, Lizeth Verónica (2018)
The present research work made it possible to synthesize the experience in the area of the Human Talent Unit, and as a specification the application of the work climate. The fulfillment of the objectives entailed as a first point the development of the diagnosis of the work climate in the National Council for Intergenerational Equality. After obtaining the results, the improvement plan was drawn up and applied, aimed at improving the work environment, and having a positive impact on the development of the work environment. The inadequate organizational climate generated the presence of negative effects such as work stress, reduced performance, job dissatisfaction, among others, all these drawbacks forced the Board to determine the importance of implementing the improvement plan, since each organization has its own characteristic of work environment. The research methodology used within this project was a deductive-inductive and statistical method, to a universe of sixty public servants, the Work Climate has been evaluated through the application of the Organizational Climate survey. The results allowed to identify negative and positive variables which served as a reference for the development of the improvement plan of the work environment.